Akkermansia muciniphila –derived L-norleucine modulates FABP1-dependent fatty acid transport - Juan Li; Zhengcai Ma; Jinyin Zhang; Chunyong Sun; Huimin Wu; Xiaoduo Li; Zheng Li; Huiqing Wang; Yubin Yang; Lianchun Shang; Zhipeng Yang; Jianyu Zhu; et al. (Proceedings of the National Academy of Sciences, 2026)
Fatty acids undergo re-esterification to form triglycerides or are directly oxidized for energy production following absorption. Fatty acid binding protein 1 (FABP1), a key transporter highly expressed in both hepatic and intestinal tissues, directs the metabolic fate of absorbed fatty acids. Although its role in facilitating fatty acid transport and lipogenesis in the liver is well established, the functional mechanisms of intestinal FABP1 remain poorly understood due to the complexity of the intestinal microenvironment. In this study, using animal models with intestinal-specific FABP1 knockout and gut microbiota depletion, we demonstrate that intestinal FABP1 directly facilitates the absorption of dietary fatty acids, and that gut microbiota regulate FABP1-mediated dietary fatty acid absorption through metabolites. Notably, the abundance of Akkermansia muciniphila exhibits an inverse correlation with FABP1-dependent obesity progression in an arachidonic acid-induced model. Supplementation with A. muciniphila markedly alleviates this obese phenotype. Through FABP1 protein-based metabolite enrichment coupled with untargeted metabolomics, we identified L-norleucine as a competitive FABP1 inhibitor despite its smaller molecular size relative to long-chain fatty acids. L-norleucine possesses a hydrophobic alkyl chain structurally analogous to fatty acids and a hydrophilic amino acid moiety, which may explain its binding to FABP1. Critically, L-norleucine constitutes a major metabolite in the gut, which may play an underappreciated role in regulating lipid homeostasis. Collectively, this study uncovers a previously unrecognized gut microbiota–FABP1 axis governing lipid homeostasis, offering therapeutic insights for metabolic disorders.